Synthesis of the repeating unit of O-specific polysaccharide isolated from the water-borne bacteria Aeromonas bestiarum 207. (1st February 2018) - Xu, Yiren; Zong, Guanghui; Jin, Shuhui; Zhang, Jianjun
Abstract: Aeromonas bestiarum 207 is a bacterial pathogen with severe impact on aquaculture. In a recent study, the structure of OPS antigens from Aeromonas bestiarum was identified as pentasaccharide repeating units. Synthesis of the pentasaccharide repeating unit and its derivative are reported. Stereo- and regio-specific synthesis was achieved under Schmidt glycosylation conditions employing appropriately protected L-rhamopyranosyl and D-glucopyranosylamine building blocks. The pentasaccharide synthesis was achieved using a [3 + 2] strategy with an overall yield of 5.2% through 11 linear steps from the monosaccharide building blocks10 and14 . Graphical abstract: Highlights: We have reported a convergent total synthesis of a pentasaccharide analogue and its tetrasccharide derivative. Stereo- and regio-specific synthesis was achieved in Schmidt glycosylation employing appropriately protected L-rhamopyranosyl and D-glucopyranosylamine building blocks. The efficient synthesis features the preparation of a key disaccharide intermediate containing an orthogonal protecting group (Lev).